(untitled) (The Review of Diabetic Studies, 2023)
Type 1 diabetes (T1D) is a chronic autoimmune disease affecting millions of people worldwide. The disease is characterized by the loss of self-tolerance to the insulin-producing β-cells in the pancreas, the destruction of β-cells, and finally the development of chronic hyperglycemia at diagnosis of T1D. Its incidence and prevalence are rising dramatically, highlighting the need for immunotherapeutic strategies able to prevent or treat the disease in a safe and specific manner. Immunotherapeutic strategies are being developed, and aim to restore immunological self-tolerance, thereby limiting unwanted immunity and β-cell destruction. Foxp3+ regulatory T (Treg) cells exert essential functions to maintain and restore immunological self-tolerance. The identification of the transcription factor Foxp3 as the specification factor for the Treg cell lineage facilitated our understanding in the biology of Treg generation and function. This review highlights the current understanding of immunotherapeutic approaches as preventative and curative measures for autoimmune T1D. It includes an overview on early immunointervention studies, which made use of general immunosuppressive agents such as cyclosporin A, followed by a discussion on newly emerging clinical trials. Besides non-antigenspecific therapies, particular attention is given to antigenspecific generation of Foxp3+ Treg cells and their potential use to limit autoimmunity such as T1D.